Remedying the abuse of organisational forms: Trusts and companies considered - LEE, Pey Woan (Institutional Knowledge at Singapore Management University, 2019)
Both the trust and the company are organisational forms distinguished bytheir ability to facilitate affirmative asset partitioning. However, this feature isvulnerable to abuse by those whose purpose is to defeat creditor rights. Thisarticle considers recent developments in judicial doctrines aimed atcountering such abuse and the extent to which they are explicable by, orcoherent, with economic analyses drawn from the work of Hansmann andKraakma.